Mutação constitucional: fundamentação e limites à luz da hermenêutica filosófica e da teoria estruturante do direito - Joao Andre Alves Lanca (2014)
The phenomenon called constitutional change was seized in the Western legal tradition, at the end of the 19th century, through the understanding that constitutions can undergo changes through informal processes in which the modification of meaning in a determined constitutional norm happens without the changing of its text. Since then, not many studies discussing constitutional changes have been done for the purpose of seeking new ways of supporting the issue and, above all, providing regulating answers and limits to it, in light of new hermeneutics conceptions and post linguistic-ontological turn constitutionalism. Within this setting, which starts at the end of the 19th century up to the beginning of this one, the main goal of this present work is to contribute to an hermeneutic grouding to the notion of informal constitutional changes, which will show itself compatible with the normative strength of the constitution and enable the elaboration of limits to its occurrence. Such task will be developed from the reading of the theme in the light of Gadamer's filosofical hermeneutics, Friedrich Müller structuring theory of law and contribuitions by Konrad Hesse. In this sense, it is argued, in the present study, a concept in the strict sense of informal constitutional change as being the concretion comprehensive phenomenom of the constitution which occurs perceptible change in the field of the norm, seized compatible way with the norm programme interpretation. In this respect, the constitutional change is here cenceived as the change occurred in the interior of the constitutional norm, that is inside the law itself and not outside of it. Finally, firmed in this way, considerations about two modalities of limits are done. the starting point being the legal text, that is the linguistic data of the constitutional arrangement. In this sense, the normative programme is pointed as a first modality of limit to the constitutional changes. Subsequently, as second modality of limits is presented, which are those parameters that could be extracted from the comprehensible horizon of the normative programme, on which are indicated two examples shared in contemporary constituitions and also shared in the Brazilian experience.